G-Quadruplexes as tools for synthetic biology - Agarwala, Prachi; Pandey, Satyaprakash; Maiti, Souvik (Chembiochem, 2013)
With the potential to engineer biological systems, synthetic biology is an emerging field that combines various disciplines of sciences. It encompasses combinations of DNA, RNA and protein modules for constructing desired systems and the rewiring of existing signalling networks. Despite recent advances, this field still lags behind in the artificial reconstruction of cellular processes, and thus demands new modules and switches to create genetic circuits. The widely characterised noncanonical nucleic acid secondary structures, G-quadruplexes are promising candidates to be used as biological modules in synthetic biology. Structural plasticity and functional versatility are significant G-quadruplex traits for its integration into a biological system and for diverse applications in synthetic circuits.
Keywords: G-quadruplexes; ribozymes; synthetic biology; topology; zipcodes

Metabolic engineering and synthetic biology for isoprenoid production in Escherichia coli and Saccharomyces cerevisiae - Navale, Govinda R.; Dharne, Mahesh S.; Shinde, Sandip S. (Applied Microbiology and Biotechnology, 2021)
Isoprenoids, often called terpenoids, are the most abundant and highly diverse family of natural organic compounds. In plants, they play a distinct role in the form of photosynthetic pigments, hormones, electron carrier, structural components of membrane, and defence. Many isoprenoids have useful applications in the pharmaceutical, nutraceutical, and chemical industries. They are synthesized by various isoprenoid synthase enzymes by several consecutive steps. Recent advancement in metabolic engineering and synthetic biology has enabled the production of these isoprenoids in the heterologous host systems like Escherichia coli and Saccharomyces cerevisiae. Both heterologous systems have been engineered for large-scale production of value-added isoprenoids. This review article will provide the detailed description of various approaches used for engineering of methyl-d-erythritol-4-phosphate (MEP) and mevalonate (MVA) pathway for synthesizing isoprene units (C-5) and ultimate production of diverse isoprenoids. The review particularly highlighted the efforts taken for the production of C-5-C-20 isoprenoids by metabolic engineering techniques in E. coli and S. cerevisiae over a decade. The challenges and strategies are also discussed in detail for scale-up and engineering of isoprenoids in the heterologous host systems.
Keywords: Escherichia coli; Isoprenoids; Metabolic engineering; Saccharomyces cerevisiae; synthetic biology

Microbial production of N-acetyl-D-glucosamine (GlcNAc) for versatile applications: biotechnological strategies for green process development - Das, Sancharini; Chowdhury, Chiranjit; Kumar, S. Pavan; Roy, Debasis; Gosavi, Suresh W.; Sen, Ramkrishna (Carbohydrate Research, 2024)
N-acetyl-D-glucosamine (GlcNAc) is a commercially important amino sugar for its wide range of applications in pharmaceutical, food, cosmetics and biofuel industries. In nature, GlcNAc is polymerised into chitin biopolymer, which is one of the major constituents of fungal cell wall and outer shells of crustaceans. Sea food processing industries generate a large volume of chitin as biopolymeric waste. Because of its high abundance, chitinaceous shellfish wastes have been exploited as one of the major precursor substrates of GlcNAc production, both in chemical and enzymatic means. Nevertheless, the current process of GlcNAc extraction from shellfish wastes generates poor turnover and attracts environmental hazards. Moreover, GlcNAc isolated from shellfish could not be prescribed to certain groups of people because of the allergic nature of shell components. Therefore, an alternative route of GlcNAc production is advocated. With the advancement of metabolic construction and synthetic biology, microbial synthesis of GlcNAc is gaining much attention nowadays. Several new and cuttingedge technologies like substrate co-utilization strategy, promoter engineering, and CRISPR interference system were proposed in this fascinating area. The study would put forward the potential application of microbial engineering in the production of important pharmaceuticals. Very recently, autotrophic fermentation of GlcNAc synthesis has been proposed. The metabolic engineering approaches would offer great promise to mitigate the issues of low yield and high production cost, which are major challenges in microbial bio-processes industries. Further process optimization, optimising metabolic flux, and efficient recovery of GlcNAc from culture broth, should be investigated in order to achieve a high product titer. The current study presents a comprehensive review on microbe-based eco-friendly green methods that would pave the way towards the development of future research directions in this field for the designing of a cost-effective fermentation process on an industrial setup.
Keywords: Genetic engineering; GlcNAc applications; Market status; Microbial bioprocess; N-acetyl-D-glucosamine; synthetic biology